2019
DOI: 10.1038/s41598-018-37998-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkali treated antioxidative crude polysaccharide from Russula alatoreticula potentiates murine macrophages by tunning TLR/NF-κB pathway

Abstract: In our previous research, Russula alatoreticula was demonstrated as a novel species, ethnic myco-food and reservoir of hot water extractable polysaccharides. However, residue after the hydrothermal process still offer plenty of medicinal carbohydrates that could easily be extracted by using alkali solvent. Thus, the present work was attempted to prepare crude polysaccharide using remainder of the conventional method and subsequently a β-glucan enriched fraction, RualaCap, was isolated. The bio-polymers display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…First of all, it was worth noting that the presence of sucrose might contribute itself to the viscosity of the solution. Also was the fact that the hydration of its molecule in the solution will reduce the amount of free water, strengthening the interaction of the CCPP molecular chain and enhancing polymerization of hydrogen bonds between the polysaccharides, thus leading to the increased viscosity of the polysaccharide solution [26][27][28][29][30][31][32][33][34][35].…”
Section: Effect Of Different Salt Concentrations and Sucrose Solutionmentioning
confidence: 99%
“…First of all, it was worth noting that the presence of sucrose might contribute itself to the viscosity of the solution. Also was the fact that the hydration of its molecule in the solution will reduce the amount of free water, strengthening the interaction of the CCPP molecular chain and enhancing polymerization of hydrogen bonds between the polysaccharides, thus leading to the increased viscosity of the polysaccharide solution [26][27][28][29][30][31][32][33][34][35].…”
Section: Effect Of Different Salt Concentrations and Sucrose Solutionmentioning
confidence: 99%
“…Thus, the increase in the expression of the surface molecules CD40, CD80 and CD86 indicates enhanced immune response. It was previously demonstrated that RAW264.7 cells play an important role as an interface between innate and adaptive immunity (15). Therefore, it was deemed necessary to investigate the effects of APS on CD40, CD80 and CD86 expression in RAW264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to build a feasible method for extracting and purifying alfalfa polysaccharides (APS) to develop new functional foods or pharmaceutical agents [13,19]. Recently, there has been an increasing number of studies that have focused on the extracting technologies, biological activities [20,21,22], and molecular mechanisms of various plant-derived polysaccharides [8,23]. However, there is still some controversy surrounding the relationship between the components and bioactivities of APS.…”
Section: Introductionmentioning
confidence: 99%